Free Flaps for Skin and Soft Tissue Reconstruction in the Elderly Patient: Indication or Contraindication - Heiko Sorg; Christian G. G. Sorg; Daniel J. Tilkorn; Simon Thönnes; Rees Karimo; Jörg Hauser (Medical Sciences, 2023)
Background: Increased lifespan and the improvement of medical treatment have given rise to research in reconstructive procedures in elderly patients. Higher postoperative complication rates, longer rehabilitation, and surgical difficulties remain a problem in the elderly. We asked whether a free flap in elderly patients is an indication or a contraindication and performed a retrospective, monocentric study. Methods: Patients were divided into two groups (YOUNG 0–59 years; OLD > 60 years). The endpoint was the survival of flaps and their dependence on patient- and surgery-specific parameters using multivariate analysis. Results: A total of 110 patients (OLD n = 59) underwent 129 flaps. The chance of flap loss increased as soon as two flaps were performed in one surgery. Anterior lateral thigh flaps had the highest chance for flap survival. Compared with the lower extremity, the head/neck/trunk group had a significantly increased chance of flap loss. There was a significant increase in the odds of flap loss in linear relation to the administration of erythrocyte concentrates. Conclusion: The results confirm that free flap surgery can be indicated as a safe method for the elderly. Perioperative parameters such as two flaps in one surgery and transfusion regimens must be considered as risk factors for flap loss.